1997
DOI: 10.1379/1466-1268(1997)002<0168:hahape>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 and Hsc70 are preferentially expressed in differentiated epithelial cells in normal human endometrium and ectocervix

Abstract: Two highly related 70K heat shock proteins, encoded by the hsc70 and hsp70 genes, are located in the nucleocytoplasmic compartment of mammalian cells. In contrast to recent cell lines, which express Hsp70 only when stressed, many human cell lines constitutively express Hsp70. The degree to which this reflects constitutive expression of Hsp70 in normal human tissues has not been extensively examined. In this study, we show by immunoblotting that human Hsp70 is constitutively expressed in the ovary, cervix, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…14 In human cells, inducible hsp70 is present in basal levels, with increased expression observed following stress treatment. 15 Generally, it is thought that members of the hsp70 family function as molecular chaperones by assisting in the refolding of other damaged proteins in response to cellular stress.…”
Section: Introductionmentioning
confidence: 99%
“…14 In human cells, inducible hsp70 is present in basal levels, with increased expression observed following stress treatment. 15 Generally, it is thought that members of the hsp70 family function as molecular chaperones by assisting in the refolding of other damaged proteins in response to cellular stress.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the HSPA family members HSPA1 [stress-inducible chaperone found to be expressed in primary tumors, but also with stress-independent expression in certain normal epithelial cells (Mangurten et al 1997;Trautinger et al 1995)] and HSPA2 [the expression of which was originally ascribed exclusively to certain testicular cell types (Huszar et al 2000;Son et al 1999), suggesting a role for HSPA2 in spermatid development/progression of spermatogenesis (Dix et al 1997;Govin et al 2006;Huszar et al 2000); however, an additional role in tumorigenesis has also been suggested (Piglowski et al 2007;Rohde et al 2005;Scieglinska et al 2008)] expression pattern have rarely been investigated in normal, non-stressed/pathological human tissues. Therefore, Scieglinska et al (2011) performed a thorough tissue-microarray based immunohistochemical study to collect new extensive data on the possible constitutive cell type-specific expression of the HSPA family members HSPA1 and HSPA2 in human somatic tissues, screening samples of 24 normal tissues derived from up to 11 donors.…”
Section: Moleculesmentioning
confidence: 99%
“…The median percentage of cells expressing hsp27 in each group was calculated. Normal cervical glands showed minimal expression of hsp27 (median: 10%, interquartile ranges [IQ]: [5][6][7][8][9][10][11][12][13][14][15]. Expression was significantly more widespread in tuboendometrial metaplasia/endometriosis (median: 35%, IQ: 15-80), cervical glandular intraepithelial neoplasia (median: 60%, IQ: 32-80), and invasive adenocarcinoma (median: 40%, IQ: 25-80) when compared with normal endocervix (P ¼ 0.007, ,0.001, and 0.001, respectively).…”
mentioning
confidence: 99%
“…It is now clear that hsps play important roles in many processes ranging from embryogenesis (12) , viral oncogenesis, cytokine effects (13) , endothelial function (14) , platelet activation (12) , growth arrest in lymphocytes, growth stimulation of some epithelial cells (15) , steroid sensitivity (16) , drug resistance (17) , and tumorigenesis (18) .…”
mentioning
confidence: 99%
See 1 more Smart Citation